1994
DOI: 10.1002/mrm.1910310317
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on the measurement of tissue T1 to monitor temperature in vivo by MRI

Abstract: Previous results for the measurement of T1 as a means of monitoring temperature have demonstrated a linear calibration with a coefficient of the order of 1.5%/degrees C. We have studied the changes in T1 further, and observe that changes in tissue perfusion are substantial contributors to the effects observed, and that the model of what is happening is complex and may not permit a simple temperature calibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 9 publications
1
31
0
2
Order By: Relevance
“…In vivo MR temperature measurements are rare and include mainly muscle [11,[27][28][29] of volunteers, seldom tumour tissue [7,30]. However, the above-mentioned MR parameters are not only sensitive to temperature but also to tissue perfusion and tissue type [11,31]. Therefore, it was our aim to design an experimental set-up including the online monitoring of tumour blood flow to improve the understanding of the complex dependencies between temperature and tumour perfusion in terms of their contribution to MR-sensitive parameters.…”
Section: Mr Thermometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo MR temperature measurements are rare and include mainly muscle [11,[27][28][29] of volunteers, seldom tumour tissue [7,30]. However, the above-mentioned MR parameters are not only sensitive to temperature but also to tissue perfusion and tissue type [11,31]. Therefore, it was our aim to design an experimental set-up including the online monitoring of tumour blood flow to improve the understanding of the complex dependencies between temperature and tumour perfusion in terms of their contribution to MR-sensitive parameters.…”
Section: Mr Thermometrymentioning
confidence: 99%
“…Once the animal was fixed, its position was not altered until the end of the MRI examination. Due to the approximate linear relationship between temperature and T1 relaxation time, this approach has been recommended for MR thermometry [18]. For calculation of T1 maps, a turbo FLASH pulse sequence [19,20] was implemented (α=15°, TE=4 ms, TR=11 ms).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Interest in this technology has been motivated by traditional high-resolution NMR applications, as well as by the growing importance of medical hyperthermia and tissue ablation. Thus, a serious need has arisen for fast, sensitive, accurate, and preferably biocompatible NMR thermal mapping techniques (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Most of the published methods involve chemical shift measurements using water or fluorocarbons as thermometric materials.…”
Section: Introductionmentioning
confidence: 99%
“…The stud- ies suggested a slight rise in T1 with heating, and a signal decrease in T1-weighted images over a limited range (28±43°). However in vivo temperature measurement based on T1 changes showed that these changes can be influenced by tissue perfusion and proton density variations [14,15]. There is a significant hysteresis existing between signal intensity and temperature [14].…”
Section: Open Mr Systemsmentioning
confidence: 99%